Jasmonate signaling pathway confers salt tolerance through a NUCLEAR FACTOR-Y trimeric transcription factor complex in Arabidopsis - Xing Li; Changjiang Li; Lei Shi; Gaofeng Lv; Xi Li; Yixuan Liu; Xiaojie Jia; Jiyuan Liu; Yuqian Chen; Lei Zhu; Ying Fu (Cell Reports, 2024)
Summary: Jasmonate (JA) is a well-known phytohormone essential for plant response to biotic stress. Recently, a crucial role of JA signaling in salt resistance has been highlighted; however, the specific regulatory mechanism remains largely unknown. In this study, we found that the NUCLEAR FACTOR-Y (NF-Y) subunits NF-YA1, NF-YB2, and NF-YC9 form a trimeric complex that positively regulates the expression of salinity-responsive genes, whereas JASMONATE-ZIM DOMAIN protein 8 (JAZ8) directly interacts with three subunits and acts as the key repressor to suppress both the assembly of the NF-YA1-YB2-YC9 trimeric complex and the transcriptional activation activity of the complex. When plants encounter high salinity, JA levels are elevated and perceived by the CORONATINE INSENSITIVE (COI) 1 receptor, leading to the degradation of JAZ8 via the 26S proteasome pathway, thereby releasing the activity of the NF-YA1-YB2-YC9 complex, initiating the activation of salinity-responsive genes, such as MYB75, and thus enhancing the salinity tolerance of plants.